(3GdfHV GdcHjQs - (3LGdjfhSs
(3ChdgG (B:s
(3bO PcQJ ai GdebGdJjf GdChdjjf ef ebGdGJ gPG GdbSe GdYdd GdJi JZjQ GdfHV ef bHd CfaSgG (B,(3gi GdJi jSei HgPG GdSHH YddkG GdYdd GdJi gi CSHGH s
(3BNQgG (B:s
(3hEf de jcf eYg YdGeGJ GdQYGa aJhbY GSJaQGZ GdNdW ef ehVY BNQ hbO bdJ ai FGeKGd gPg GdCTjGA cdgG bhdG TGajkG ai cJGH GdHMQGf JeJ GdebGdI GdSGOSI YTQI s
(3LYdg LGdjfhS ai SJ YTQI ebGdIs
(3bSegG CQHYI CLRGA ai cd LRA CQHY ebGdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B265 s
(3eUOQ GbJfGA GdCUd (B:s
(3cJGHNGfI eQcRi LGeYI WgQGf (B(2408) s
Keywords: (3GdWHs